PSXVI-21 The New Mexico Youth Ranch Management Camp: A Collaborative Effort to Educate Youth in Sustainable Ranch Management Practices. (7th December 2018) - Ward, M; Blandford, J; Gordon, S; Boyd, J; Lucero, S; McCarty, J; Marez, L; Torres, P; Dean, T; Cram, D; Gifford, C; Smallidge, S
Abstract: Less than 2% of the U.S. population is involved in agriculture. Of this population, the average age of active livestock producers is 58. Given this reality, youth education and involvement in agriculture is needed to sustain and grow this very important industry. The New Mexico Youth Ranch Management Camp is a one-of-a kind intensive learning program designed to educate high school aged students in beef production and natural resource management. The goal is for participants to acquire practical, science-based skills that are employed on modern-day ranches to advance beef production, natural resource stewardship, wildlife management and economics. Each day of the camp focuses on one of these facets to ranch management. Participants also have the unique opportunity to learn from members of the host ranch. The CS Ranch is a historic working ranch located in northern New Mexico. At the beginning of the camp, teams of 4 to 5 participants are formed. These teams must develop a ranch plan, incorporating skills learned during the week of instruction. At the conclusion of the week, teams presents their plan to a panel of judges. This is an extensive collaboration among the NMSU Extension Specialists, County Extension Agents and ranching stakeholders from New Mexico and Texas. The camp creates a unique learning opportunity for youth to acquire a knowledge base and skill set in ranch management. The scholastic level of material presented during the camp is such that participants who go on to attend NMSU receive 3 hours of academic credit towards their degree. This program has educated over 175 New Mexico youth. Participant evaluations indicate a significant increase in knowledge in all topics presented. Fifty-five % of participants have gone to college and majored in an agriculture related field.